William the Curious : Knight of the Water Lilies - Santore, Charles (New York : Random House, 1997)
A lowly frog teaches a beautiful queen about the dangers of pollution.
School Library Journal
Bulletin (Center for Children's books)
5.5
K-3
Keywords: Frogs -- Fiction; Kings, queens, rulers, etc. -- Fiction; Pollution -- Fiction; Environmental protection -- Fiction; Frogs -- Fiction; Queens -- Fiction; Pollution -- Fiction; Environmental protection -- Fiction